An ethnobotanical study of plants used to treat liver diseases in the Maritime region of Togo. (2nd April 2016) - Kpodar, Madje S.; Karou, Simplice D.; Katawa, Gnatoulma; Anani, Kokou; Gbekley, Holaly E.; Adjrah, Yao; Tchacondo, Tchadjobo; Batawila, Komlan; Simpore, Jacques
Abstract: Ethnopharmacological relevance: In Togo, many persons still rely on plants for healing, however very little is known about the medicinal practices of the indigenous people. The present study aimed to document the medicinal plant utilization for the management of liver diseases in the Maritime region of the country. Methodology: This was an ethnobotanical survey conducted in the Maritime region of Togo from June to August 2015. The data were gathered from 104 traditional healers (TH) by direct interviews using a semi-structured questionnaire. The calculated use values (UV) were used to analyze the importance of the cited plants. Results: A total of 99 plant species belonging to 88 genera and 49 families were cited by the TH as curing the hepatic diseases. The most represented families were Caesalpiniaceae with 8 species, followed by Euphorbiaceae with 7 species, Apocynaceae and Asteraceae with 6 species each. The highest UV were recorded with Gomphrena celosioides (0.13), Xylopia ethiopica (0.12), Senna occidentalis (0.12), Bridelia ferruginea (0.12), Cymbopogon citratus (0.12), Kigellia Africana (0.09), Cassia sieberiana (0.08) and Sanseviera liberica (0.08), showing their importance in the management of liver dysfunction in the surveyed region. The main used parts were the leaves, followed by the roots, the whole plant, the rhizome and the bark, accounting for more than 10% each. The herbal medicines were mostly prepared in the form of decoction and administrated by oral route. Conclusion: This study showed that Maritime region of Togo has an important plant biodiversity that is exploited by the indigenous TH. However, some plants cited by the TH have not been studied for their possible hepatoprotective effects. These plants are therefore a starting point for biological screenings. Graphical abstract: